Autentisitas Manusia Menurut Albert Camus - Agustinus Widyawan; Purnomo Putra (Parahyangan Catholic University, 2020)
Humanity is unable to achieve grasp over the world so filled with mysteries. As a result, his life becomes limited. Although Humanity continues to hope, his limitations however see to it that human hope can crumble at any given moment. Based on these facts, human life becomes an absurdity. The absurdity of life throws man into an existence of the incomprehensible mystery of life. Albert Camus offers a way of life (modus vivendi) for him to survive this absurdity. He offers the authenticity of human life. This authenticity enables us to live as homo vivens. Homo vivens refer to those who live according to their true vocation as creators and directors of their own lives.